Формування архітектурно-планувальних вирішень готелів Марокко - Аззауі, Хішам; Azzaui, Khisham (Видавництво Львівської політехніки, 2022)
У статті проаналізовано принципи розміщення будівлі готелю на території ділянки, основних і допоміжних блоків; визначення основних функціональних зон, репрезентативної зони, зон автостоянок, спортивних зон, відпочинку і рекреацій; вирішення пішохідно-транспортних комунікацій на території ділянки: в’їзду – виїзду спеціального транспорту, автостоянки наземного і підземного паркінгу, схем пішохідних комунікацій; озеленення зовнішніх і внутрішніх просторів: спеціальних насаджень, газонів, квітників, альпінаріїв, влаштування шумозахисних і зон візуального споглядання. Визначено основні типи готельних комплексів Марокко.

The article analyzes the principles of placing the hotel building on the site, the main and auxiliary blocks; the definition of the main functional zones, representative zone, parking zones, sports and recreation zones; the solution of pedestrian-transport communications on the site: entrance/exit of special transport, parking ground and underground parking, pedestrian communication schemes; landscaping of external and internal spaces: special plantings, lawns, flower beds, rock gardens, noise protection and visual contemplation zones. The main types of hotel complexes in Morocco are identified: hotel complexes with a centralized layout, hotel complexes with a block layout, hotel complexes with a podium layout, hotel complexes with a simplified layout, hotel complexes with a compact layout, hotel complexes with a complicated layout, hotel complexes with an atrium layout. Modern hotel complexes are designed to create comfortable living conditions for the guest and provide a range of additional services. This turns hotels into semi-functional structures that combine different types of functional premises in one building, namely: residential, administrative, public premises, engineering and utility rooms.
Formation of architectural planning solutions of Morocco hotels
Keywords: готель; готельний комплекс; полі функціональні будівлі; об’ємно-планувальні рішення; типи готельних будівель; Марокко; hotel; hotel complex; poly-functional buildings; spatial planning solutions; types of hotel buildings; Morocco; 72.01; 621.711.168